Catecholamines profiles at diagnosis: Increased diagnostic sensitivity and correlation with biological and clinical features in neuroblastoma patients. (February 2017) - Verly, Iedan R.N.; van Kuilenburg, André B.P.; Abeling, Nico G.G.M.; Goorden, Susan M.I.; Fiocco, Marta; Vaz, Frédéric M.; van Noesel, Max M.; Zwaan, C. Michel; Kaspers, GertJan L.; Merks, Johannes H.M.; Caron, Huib N.; Tytgat, Godelieve A.M.
Abstract: Introduction: Neuroblastoma (NBL) accounts for 10% of the paediatric malignancies and is responsible for 15% of the paediatric cancer-related deaths. Vanillylmandelic acid (VMA) and homovanillic acid (HVA) are most commonly analysed in urine of NBL patients. However, their diagnostic sensitivity is suboptimal (82%). Therefore, we performed in-depth analysis of the diagnostic sensitivity of a panel of urinary catecholamine metabolites. Patients and methods: Retrospective study of a panel of 8 urinary catecholamine metabolites (VMA, HVA, 3-methoxytyramine [3MT], dopamine, epinephrine, metanephrine, norepinephrine and normetanephrine [NMN]) from 301 NBL patients at diagnosis. Special attention was given to subgroups, metaiodobenzylguanidine (MIBG) non-avid tumours and VMA/HVA negative patients. Results: Elevated catecholamine metabolites, especially 3MT, correlated with nine out of 12 NBL characteristics such as stage, age, MYCN amplification, loss of heterozygosity for 1p and bone-marrow invasion. The combination of the classical markers VMA and HVA had a diagnostic sensitivity of 84%. NMN was the most sensitive single diagnostic metabolite with overall sensitivity of 89%. When all 8 metabolites were combined, a diagnostic sensitivity of 95% was achieved. Among the VMA and HVA negative patients, were also 29% with stage 4 disease, which usually had elevation of other catecholamine metabolites (93%). Diagnostic sensitivity for patients with MIBG non-avid tumour was improved from 33% (VMA and/or HVA) to 89% by measuring the panel. Conclusions: Our study demonstrates that analysis of a urinary catecholamine metabolite panel, comprising 8 metabolites, ensures the highest sensitivity to diagnose NBL patients. Highlights: Eight catecholamine metabolites have a diagnostic sensitivity of 95%; VMA and HVA have a diagnostic sensitivity of 84%. Normetanephrine is the most sensitive marker for neuroblastoma (NBL) diagnostics (89%). 3-methoxytyramine correlates the best with NBL high-risk features. Twenty-nine percent of the VMA and HVA non-excreting patients have a stage IV disease. Metaiodobenzylguanidine non-avid tumours excrete VMA and HVA in 33%, while other metabolites excrete in 89%.